2018
DOI: 10.2298/tsci170126121d
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the inlet opening on mixed convection inside a 3-D ventilated cavity

Abstract: Mixed convection heat transfer in a 3-D ventilated cavity is studied numerically using finite volume method. The results are presented in terms of streamlines, temperature distribution, velocity fields, and average Nusselt number for different combinations of thermal and geometrical controlling parameters, namely, Reynolds number, Re = 100, Richardson number (0.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 24 publications
(23 reference statements)
0
8
0
Order By: Relevance
“…A recent 3-D numerical investigation of the inlet opening effect on the mixed convection inside a 3-D ventilated cavity was presented by Doghmi et al [29]. They concluded that the global average Nusselt number at the active walls increases with increasing Richardson numbers and the heat transfer rate increase and decrease at the hot and the cold wall respectively by increasing the inlet opening cross-section.…”
Section: Ra 10mentioning
confidence: 99%
“…A recent 3-D numerical investigation of the inlet opening effect on the mixed convection inside a 3-D ventilated cavity was presented by Doghmi et al [29]. They concluded that the global average Nusselt number at the active walls increases with increasing Richardson numbers and the heat transfer rate increase and decrease at the hot and the cold wall respectively by increasing the inlet opening cross-section.…”
Section: Ra 10mentioning
confidence: 99%
“…The obstacle and cavity dimensions have an influence on the flow and thermal behaviors. Mixed convection heat transfer has been studied by a number of researchers such as [15], [16], [17], [18], [19], [2] and [20]. Pourmahmoud, Ghafouri and Mirzaee [15] investigated numerically the laminar mixed convection in a cavity employed water-Al2O3, water-Cu or water-TiO2 nanofluids as medium work.…”
Section: Introductionmentioning
confidence: 99%
“…The maximum values are obtained when using Cu nanoparticles. Mahmoodi [17] studied the mixed convection heat transfer in a 3-D ventilated cavity numerically with finite volume method. The results indicated that the flow intensity and the heat transfer rate are enhanced by an optimal choice of the Re, Ri, relative height of the openings and relative width of the openings.…”
Section: Introductionmentioning
confidence: 99%
“…In the literature, some investigation of the mixed convection in vented cavities were reported using different inlet and outlet ports location [17][18][19][20], uniform and non-uniform heated wall [21][22][23][24], adiabatic ,isothermal or heated solid block with different shape, size location and [25][26][27][28][29][30][31][32][33]. Gupta et al [34] studied a mixed convection in a ventilated cavity for different thermal conditions of the cavity walls with heated conducting cylinder at the size of D (0.1-0.5) and conductivity K (0.1-10).Considering two cases of heated walls.…”
Section: Introductionmentioning
confidence: 99%